2001
DOI: 10.1080/02652040010018128
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of regular sized Ca-alginate microspheres using membrane emulsification method

Abstract: Monodisperse Ca-alginate microspheres were prepared using the membrane emulsification method. Three ionic types of drugs (anionic, cationic and non-ionic) were incorporated into the microspheres, and the effects of sodium alginate concentration and the pressure applied during the dispersing process on the properties of the microspheres were examined. Monodisperse microspheres were obtained when the concentration of alginate solution was 2 wt% and the pressure applied was 0.4 x 10(5) Pa. The mean size of micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(7 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The zeta potential of the microspheres ranged from -11.7 ± 0.05 to -22.0 ± 0.03, and similar mV values from -0.68 to -16 have been reported for alginate microspheres (You et al, 2001;Tello et al, 2015). This potential is the product of the reaction between sodium alginate and calcium chloride at different concentrations.…”
Section: Morphology Size and Zeta Potential Of Lacticaseibacillus Par...supporting
confidence: 75%
“…The zeta potential of the microspheres ranged from -11.7 ± 0.05 to -22.0 ± 0.03, and similar mV values from -0.68 to -16 have been reported for alginate microspheres (You et al, 2001;Tello et al, 2015). This potential is the product of the reaction between sodium alginate and calcium chloride at different concentrations.…”
Section: Morphology Size and Zeta Potential Of Lacticaseibacillus Par...supporting
confidence: 75%
“…For example, sodium alginate (Na-alginate) is extruded dropwise through a needle into a solution of divalent cations, which induces crosslinking of the guluronic residues of the alginate polymer [11][12][13][14]. The alternative techniques are as follows: (i) atomization (spray-drying) [15,16], (ii) coacervation [17], (iii) emulsification (internal/external gelation) [18][19][20][21] and other methods. However, all of these techniques have well-known drawbacks such as unstable yield, tedious procedures and non-uniform particle sizes with a wide size distribution.…”
Section: Introductionmentioning
confidence: 99%
“…The insoluble behavior of chitosan would prevent the anthocyanin in rose petals from dissolving into alginate gel solution, providing a beneficial effect on the preservation of anthocyanin (Tirtashi et al, 2019). Moreover, the positive charge of chitosan (Guo, Ping, Jiang, Huang, & Tong, 2003) can inhibit the change of anthocyanin structure in the rose even when contact with sodium alginate with a negative charge (You et al, 2001). In summary, by comparing the degradation rate of anthocyanins, it was found that 1% chitosan and peanut oil coatings had a better color protection effect.…”
Section: Evaluation Of the Color Protection Effect Of Color Protectmentioning
confidence: 96%